Strategi pemasaran pada the alena resort ubud di kabupaten gianyar bali - Sumerta, I Wayan Adi; Widyatmaja, I Gusti Ngurah; Sulistyawati, Agung Sri (Jurnal Kepariwisataan dan Hospitalitas, 2019)
This research conducted at The Alena Resort Ubud, in Gianyar Regency, Bali. This new hotel often hasn’t reached its occupancy target for several months and the competition in Ubud is getting higher, so this research needs to be done to find out the marketing mix used by The Alena Resort and determine good marketing strategies to achieve the expected occupancy target. The type of data used is qualitative data and quantitative data. Data collection is done by observation, interviews, questionnaires, literature studies, and documentation. The sampling technique uses the Slovin formula and accidental sampling technique. Data analysis techniques used Likert scale analysis and SWOT analysis. The results showed that the 8P activities conducted by The Alena Resort got responses from tourists who stayed at The Alena Resort, and most of the statement were declared good and very good, but there are some things that still need to be evaluated because they were declared good enough and unfavorable statements from tourists. Based on the SWOT analysis, several strategies have been created, such as: strategy to expand relationships with business partners or travel agents, strategy to improve promotion through social media, strategy to create new tourist attractions in the hotel area and improve access to hotel, strategy to add vegetarian menus for breakfast and add pool chair, strategy to expand domestic market targets, strategy to create new product variations such as wedding packages, strategy to improve product and service quality, and strategy to maintain hotel brand image. Suggestions that can be given to The Alena Resort are, It is necessary to evaluate the marketing mix activities that has been conducted and apply the marketing strategies that has been created in this research for The Alena Resort.